CORPORATE GOVERNANCE AND THE FINANCIAL PERFORMANCE OF DEPOSIT MONEY BANKS (DMBS) IN NIGERIA - Abdulrahman, Shehu; Khalid, Garba (International Journal For Research In Business, Management And Accounting, 2019)
The study examines the relationship that exists between some selected corporate governance mechanisms and the financial performance (ROE) in the consolidated banks by using ten selected Deposit Money Banks (DMBS) in Nigeria. For the purpose of this study, data were collected from annual financial reports of concerned financial institutes from 2010 - 2014 by using simple random sampling technique without replacement. The data were analyzed by using correlational analysis with the helped of the output from SPSS Version 16.0. The study found that a significant negative relationship exists between Board size (BS), Non-executive Directors (NED) and the financial performance (i.e. Returns on Equity ROE). The study therefore, recommends that steps should be taken for mandatory compliance with the code of corporate governance while an effective legal framework should be developed and be provided for effective enforcement of the law.